RELAÇÃO DA METIONINA MAIS CISTINA COM A LISINA EM RAÇÕES PARA ALEVINOS DE TAMBAQUI (Colossoma macropomum) - SOUZA, Flávio Oliveira (2014)
The aim was to determine the methionine plus cystine with lysine ratio in diets for tambaqui (Colossoma macropomum) fingerlings. Six hundred tambaqui fingerlings of two distinct initial weights, 0.28 ± 0.08g and 0.94 ± 0.33g, were used in an experiment with randomised block design (criterion dependent upon initial average weight) composed of six treatments, five repetitions in two blocks and twenty fish per experimental unit. The treatments consisted of six experimental diets isolysinic digestible (1.45%), isoenergetic, isophosphorus and isocalcium containing different methionine plus cystine with digestible lysine ratio (50, 55, 60, 65, 70 and 75%). The fish were kept in 1,000 litre polyethylene tanks, equipped with individual aeration and water supplies, and were fed ad libitum in six daily meals for 45 days. Performance parameters, body composition, protein and body fat deposition and the efficiency nitrogen retention of the fishes were evaluated. The increase of the dietary digestible methionine plus cystine:lysine ratio in the diet affected the specific growth rate, feed:gain ratio, digestible methionine plus cystine intake and the body fat of the fishes. The effects were quadratic for the first two, with these variables improving up to methionine plus cystine:lysine ratio of 64.4% and 64.8%. The digestible methionine plus cystine intake increased and body fat decreased linearly with increase of methionine plus cystine:lysine ratio. The methionine plus cystine with lysine digestible ratio recommended in diets for tambaqui fingerlings is 64.8%, which corresponds the level of digestible methionine plus cystine of 0.94% (0.313% Mcal of ED).